Disorienting the logical - Egumenovska, Kristina (Teorija in praksa, 2014)
This paper presents an analysis of video games by focusing on the gaming process and its uniquely dynamic configuration (e.g. psychological/semiotic, aesthetic, and potentially political). It first explores the two major challenges that make a strong rationale for such a focus and then it goes on to define video games in reference to the question they formally share with calligraphic practice. Lastly, the paper considers the specific influence of manga, the Japanese comic art, on the (de)sign of video games as a way to further probe into their engaging semiotic dynamics. Formally and thematically, the analysis shows that video games are evocative of the way we engage with the world through the gestural regimes of language and imagination.
Keywords: computer games; Domišljija; Imagination; jezik; Language; manga; Poetics; Poetika; Video games; Videoigre